Clumped isotope constraints on equilibrium carbonate formation and kinetic isotope effects in freezing soils. (15th August 2018) - Burgener, Landon K.; Huntington, Katharine W.; Sletten, Ronald; Watkins, James M.; Quade, Jay; Hallet, Bernard
Abstract: The clumped and stable isotope (Δ47, δ 18 O, and δ 13 C) composition of pedogenic (soil) carbonates from cold, arid environments may be a valuable paleoclimate archive for climate change-sensitive areas at high latitudes or elevations. However, previous work suggests that the isotopic composition of cold-climate soil carbonates is susceptible to kinetic isotope effects (KIE). To evaluate the conditions under which KIE occur in cold-climate soil carbonates, we examine the Δ47, δ 18 O, and δ 13 C composition of soil carbonate pendants from Antarctica (Dry Valleys, 77°S), the High Arctic (Svalbard 79°N), the Chilean and Argentinian Andes, and the Tibetan plateau (3800–4800 m), and compare the results to local climate and water δ 18 O records. At each site we calculate the expected equilibrium soil carbonate Δ47 and δ 18 O values and estimate carbonate Δ47 and δ 18 O anomalies (observed Δ47 or δ 18 O minus the expected equilibrium Δ47 or δ 18 O). Additionally, we compare the measured carbonate δ 13 C to the expected range of equilibrium soil carbonate δ 13 C values. To provide context for interpreting the Δ47 and δ 18 O anomalies, the soil carbonate results are compared to results for sub-glacial carbonates from two different sites, which exhibit large Δ47 anomalies (up to −0.29‰). The Antarctic and 4700 masl Chilean Andes samples have negative Δ47 anomalies and positive δ 18 O anomalies consistent with KIE due to rapid bicarbonate dehydration during cryogenic carbonate formation. In contrast, the lower elevation Chilean Andes, Argentinian Andes, Tibetan Plateau and High Arctic results are consistent with equilibrium, summer carbonate formation. We attribute the differences in Δ47 and δ 18 O anomalies to variations in inter-cobble matrix grain size and its effects on the effective soil pore space, permeability (hydraulic conductivity), moisture, and bicarbonate dehydration rate. The Antarctic and 4700 masl Chilean Andean soils have coarse-grained matrices that facilitate rapid bicarbonate dehydration. In contrast, the lower elevation Chilean Andes, Argentinian Andes, High Arctic and Tibetan Plateau soils have finer-grained matrices that decrease the soil pore space, soil permeability and CO2 gas flux, promoting equilibrium carbonate formation. The sub-glacial carbonate samples yield highly variable Δ47 and δ 18 O anomalies, and we propose that the differences between the two glacier sites may be due to variations in local sub-glacial drainage conditions, pCO2, and pH. Our findings suggest that carbonates from soils with coarse-grained matrices may exhibit KIE in cold climates, making them poor paleoclimate proxies. Soils with fine-grained matrices are more likely to yield equilibrium carbonates suitable for paleoclimate reconstructions regardless of climate. Paleosol matrix grain size should therefore be taken into account in the evaluation of carbonate stable and clumped isotope values in paleoclimate studies.